2013
DOI: 10.1152/ajpendo.00067.2013
|View full text |Cite
|
Sign up to set email alerts
|

Excess TSH causes abnormal skeletal development in young mice with hypothyroidism via suppressive effects on the growth plate

Abstract: Hypothyroidism in the young leads to irreversible growth failure. hyt/hyt Mice have a nonfunctional TSH receptor (TSHR) and are severely hypothyroid, but growth retardation was not observed in adult mice. We found that epiphysial cartilage as well as cultured chondrocytes expressed functional TSHR at levels comparable to that seen in the thyroid, and that addition of TSH to cultured chondrocytes suppressed expression of chondrocyte differentiation marker genes such as Sox-9 and type IIa collagen. Next, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…TSH has been identified to have direct effects on these tissues independently of thyroid hormone [6][7][8]. In 2013, Endo et al reported that TSHR was highly expressed in cartilage tissue at levels comparable to that seen in the thyroid [9]. However the effects of TSH on chondrocyte behavior remain unclear.…”
mentioning
confidence: 99%
“…TSH has been identified to have direct effects on these tissues independently of thyroid hormone [6][7][8]. In 2013, Endo et al reported that TSHR was highly expressed in cartilage tissue at levels comparable to that seen in the thyroid [9]. However the effects of TSH on chondrocyte behavior remain unclear.…”
mentioning
confidence: 99%
“…[3] A high serum TSH level causes abnormal skeletal development in hypothyroidism via its suppressive effects on the growth plate. [4] The delay in diagnosis -as in our case -severely affected the skeleton and mental development. [5] Through this letter, we highlight the importance of early diagnosis of hypothyroidism and the need for a high index of suspicion in obese children with hip pain.…”
Section: Lettermentioning
confidence: 50%
“…Thus, in the overt form of hypothyroidism, the spatial and temporal balance between proliferation and differentiation of chondrocytes is altered leading to accumulation of chondrocytes that did not acquire adequate hypertrophic morphology. In addition, it was previously demonstrated that the TSH receptor was expressed on growth plate chondrocytes and that over expression of TSH in mice lead to a decreased height of the growth plate [30]. These fi ndings point that in the overt form of hypothyroidism, TH/TSH balance does not favor the proliferation of chondrocytes, while in the subclinical form the proliferation capacity of chondrocytes is preserved at a nearly normal rate.…”
Section: Discussionmentioning
confidence: 96%
“…It is well-known that TH are important for type 10 collagen synthesis and fi nal differentiation of the growth plate chondrocytes to hypertrophic ones [35]. Independently, TSH has the same effect [30]. It is also known that an adequate amount of type 10 collagen is important for cartilage calcifi cation [36].…”
Section: Discussionmentioning
confidence: 99%